1988
DOI: 10.1001/jama.1988.03720160029025
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-effectiveness of Cervical Cancer Screening for Low-Income Elderly Women

Abstract: Controversy surrounds prevention policy for the elderly. While some cost-effectiveness analyses have been done for the general elderly population, to our knowledge no study has examined the provision of preventive services to a low-income elderly population. We conducted a study of the cost-effectiveness of a cervical cancer screening program for infrequently screened elderly women attending an urban municipal hospital clinic. The results of Papanicolaou testing were abnormal (malignant or premalignant) in 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A similar measure was adopted by Mandelblatt and Fahs, who reported that the early detection of cervical cancer through Pap tests saved 3-7 years of life per 100 tests and represented a cost of $2874 per life year saved. 4 Oster and Epstein also used years of life saved as a measure of effectiveness in their study of antihyperlipaemic therapy in the prevention of coronary heart disease.5…”
Section: Measures Ofeffectivenessmentioning
confidence: 99%
“…A similar measure was adopted by Mandelblatt and Fahs, who reported that the early detection of cervical cancer through Pap tests saved 3-7 years of life per 100 tests and represented a cost of $2874 per life year saved. 4 Oster and Epstein also used years of life saved as a measure of effectiveness in their study of antihyperlipaemic therapy in the prevention of coronary heart disease.5…”
Section: Measures Ofeffectivenessmentioning
confidence: 99%
“…5 Consider the example of the Pap smear. CEA has shown that a onetime Pap smear for elderly African American women saves money, 6 whereas the annual Pap smears that are the standard for well-insured women cost-in today's dollars-more than $2 million per life year compared with less frequent screening. 7 If CEAs were used to allocate resources, the annual Pap smear would be a thing of the past, and women who rarely or never receive Pap smears would get them at least every 5 years.…”
mentioning
confidence: 99%